2017
DOI: 10.1111/1462-2920.13658
|View full text |Cite
|
Sign up to set email alerts
|

Oscillospira and related bacteria – From metagenomic species to metabolic features

Abstract: Oscillospira is an under-studied anaerobic bacterial genus from Clostridial cluster IV that has resisted cultivation for over a century since the first time it was observed. In recent years its 16S rRNA gene was identified in several human gut microbiota studies where it was often associated with interesting traits, especially leanness. However, very little is known about its metabolism or physiology. Here we used nearly complete genomes derived from shot-gun metagenomic data from the human gut to analyze Osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
238
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(254 citation statements)
references
References 53 publications
14
238
2
Order By: Relevance
“…Oscillospira is actually an enigmatic bacterial genus, butyrate producer that may contribute to the formation of secondary bile acids and known to prevent Clostridium difficile- associated infectious disease (CDAD) in humans 26,30,31 . Poultry represents a possible reservoir of C .…”
Section: Discussionmentioning
confidence: 99%
“…Oscillospira is actually an enigmatic bacterial genus, butyrate producer that may contribute to the formation of secondary bile acids and known to prevent Clostridium difficile- associated infectious disease (CDAD) in humans 26,30,31 . Poultry represents a possible reservoir of C .…”
Section: Discussionmentioning
confidence: 99%
“…Essential impact of the EH on microbiota during heat stress is manifested in elevated number of beneficial bacteria ( Eubacterium, Lactococcus, Oscillospira, Roseburia, Vallitalea). Roseburia , Eubacterium and Oscillospira are butyrate‐producing bacterial genera, positively correlate with antioxidant activities and negatively correlate with inflammation (Gophna et al, ; Wang et al, ). Our results are consistent with previously in vitro study of Possemiers et al (), who showed that yeast fermentate induces butyrate production and possess anti‐inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…The specific functions of the genus Oscillospira are unclear due to the fact that it has not been cultured (Konikoff & Gophna, ). In humans, relative abundances of this genus increase when individuals are feeding on animal‐based diets (David et al., ), and genome reconstruction from metagenomic analysis of the human gut microbiota suggests that human‐associated species of Oscillospira utilize host‐produced sugars (Gophna, Konikoff, & Nielsen, ). However, in other animals, the genus Oscillospira has been hypothesized to play roles in fibre fermentation, given its presence in the guts of many ruminants and other herbivores (Kohl & Dearing, ; Mackie et al., ).…”
Section: Discussionmentioning
confidence: 99%